Primate occurrence in the Upper Paraguay River Basin and Pantanal, Brazil - Tomas, Walfrido Moraes; Timo, Thiago Philipe de Camargo; Camilo, André Restel; Oliveira, Maxwell da Rosa; Tortato, Fernando Rodrigo; Mamede, Simone; Benites, Maristela; Garcia, Carolina Martins; Gusmão, Almério Câmara; Rimoli, José (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2022)
The Upper Paraguay River Basin (UPRB), where the Pantanal wetland is located, is placed in the center of South America, and has contact zones with various biomes such as the Amazon rainforest, Cerrado, Atlantic Forest, the Chaco, and Bolivia’s Chiquitano Forest. The Cerrado has the greatest influence on the region’s vegetation, but the aforementioned biomes also have an impact on the vegetation and fauna, even within the Pantanal floodplains. When compared to other ecosystems, the Upper Paraguay River Basin has little endemism, and the Pantanal even less. Out of the more than 127 primate species reported for Brazil to this date, eight species occur in the UPRB: Aotus azarae (Humboldt 1811), Alouatta caraya (Humboldt 1812), Ateles chamek (Humboldt, 1812), Sapajus cay (Illiger 1815), Callithrix penicillata (E. Geoffroy 1812), Mico melanurus (É. Geoffroy 1812), Plecturocebus sp., and Pithecia mittermeieri (Marsh, 2014). The Pantanal floodplain is home to five of these species: A. azarae, A. caraya, S. cay, C. penicillata, and M. melanurus. This article describes the species found in the region and provides additional information on their distribution. Furthermore, we present evidence for the inconsistency of Plecturocebus pallescens and P. donacophilus in the area, indicating the need for taxonomic studies to resolve these uncertainties.